Fruitlessness of Anti-Corruption Agencies: Lessons from the Commission on Human Rights and Administrative Justice in Ghana - Asamoah, K.; Ofosu-Mensah, E.A. (Journal of Asian and African Studies, 2018)
Political corruption has become one of the most topical issues in the political discourse in Ghana. This stems from the fact that corruption has become so endemic and systemic in Ghanaian polity with its negative effects on the economy. Indeed, political corruption negatively affects job creation, investment potentials, infrastructural development and generally the standard of living of the people. It is within this context that anti-corruption institutions have been established in Ghana to address the menace of corruption. The Commission on Human Rights and Administrative Justice (CHRAJ) is one of such institutions established under the 1992 Republican Constitution of Ghana tasked with the responsibility of addressing the problem of corruption in Ghanaian public administration system. This paper examines the extent to which the Commission has achieved this constitutional mandate of addressing the problem of corruption. The study finds that some drawbacks which inhibit the potency of CHRAJ in addressing the problem of corruption include lack of political will by the governing elite to support the institution, eroding confidence of the Commission, the trend of appointing the Head of the Commission in an acting capacity, constitutional weaknesses, poor capacity building support and low motivation. The paper therefore offers pragmatic policy suggestions to address the inherent deficiencies of the Commission with the objective of making it more functional.
Keywords: Ombudsman; Corruption; Africa; Ghana; Effectiveness; Political will